2004
DOI: 10.1021/nl049401t
|View full text |Cite
|
Sign up to set email alerts
|

Self-Aligned, Gated Arrays of Individual Nanotube and Nanowire Emitters

Abstract: We demonstrate the production of integrated-gate nanocathodes which have a single carbon nanotube or silicon nanowire/whisker per gate aperture. The fabrication is based on a technologically scalable, self-alignment process in which a single lithographic step is used to define the gate, insulator, and emitter. The nanotube-based gated nanocathode array has a low turn-on voltage of 25 V and a peak current of 5 µA at 46 V, with a gate current of 10 nA (i.e., 99% transparency). These low operating voltage cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
103
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 30 publications
0
103
0
Order By: Relevance
“…Controlled growth of well-ordered Er-doped SiNWs is crucial, and would eliminate much of the processing associated with device fabrication. Selective growth of SiNWs via a VLS mechanism were achieved using an ion implantation mask, (Sood et al, 2006) lithographically defined regions of SiNW growth by thin film evaporation (Gangloff et al, 2004;Islam et al, 2004) and seeding colloids (Hochbaum et al, 2005). These methods employ expensive or complex processing techniques, but are unfit for the controlled growth of SiNWs and selective coating of Er-doped solutions at the same time.…”
Section: Controlled Pl Of Er-doped Silicon Nanowiresmentioning
confidence: 99%
“…Controlled growth of well-ordered Er-doped SiNWs is crucial, and would eliminate much of the processing associated with device fabrication. Selective growth of SiNWs via a VLS mechanism were achieved using an ion implantation mask, (Sood et al, 2006) lithographically defined regions of SiNW growth by thin film evaporation (Gangloff et al, 2004;Islam et al, 2004) and seeding colloids (Hochbaum et al, 2005). These methods employ expensive or complex processing techniques, but are unfit for the controlled growth of SiNWs and selective coating of Er-doped solutions at the same time.…”
Section: Controlled Pl Of Er-doped Silicon Nanowiresmentioning
confidence: 99%
“…Nanowires and nanotubes have been proved to exhibit excellent field emission properties due to their high aspect ratio and tip-like shape which maximize the geometrical field enhancement (Au et al, 1999;Wong et al, 1999;Nilsson et al, 2000). Another important device demonstrated using site-determined vertical nanowires is the self-aligned, gated arrays of individual nanotubes/nanowire emitters (Gangloff et al, 2004). The fabrication process of the device is shown in Fig.…”
Section: Patterned Growth Of Vertical Nanowiresmentioning
confidence: 99%
“…As a result their use as electron sources for field emission based flat panel displays has been greatly explored, with the emergence of prototype displays. 4 While extensive two terminal field emission measurements have been performed, [2][3][4][5][6] considerably fewer three terminal studies [7][8][9][10] have been undertaken and those that have been performed have often been from arrays of nanotubes. In this letter we demonstrate a method of examining the gated field emission properties of an individual CNT and a method for establishing the gate transparency factor and the shielding of the emitter due to the presence of the gate itself.…”
mentioning
confidence: 99%
“…Nanotube emitters 7 when arranged individually in a gate well emit 40 nA to the gate electrode at a gate bias of 40 V, which corresponds to a gate transparency, defined as the ratio of emission current collected at the anode to emission current collected at the gate, of 99%. Work on nanostructured carbon 8 as electron sources utilized a transmission electron microscopy grid as the gate electrode, placed 55 m from the cathode which resulted in high gate turn on voltages of 220 V; however, a gate transparency of only 50% is calculated at maximum emission of 10 A. Guillorn et al 9 reported the use of carbon nanofibers as electron sources with a relatively high gate voltage of 85 V required for an emission from the CNF of 0.3 A; however, this corresponds to a high gate transparency of 99%.…”
mentioning
confidence: 99%
See 1 more Smart Citation